Analysis of relative profitability of key Ugandan agricultural enterprises by agricultural production zone - Kraybill, David; Kidoido, Michael (International Food Policy Research Institute, 2009)
Uganda's economy remains heavily reliant on the agricultural sector. The agricultural sector contributes about 90 percent of total export earnings, generates about 23.7 percent of total Gross Domestic Product (GDP), and directly or indirectly provides a livelihood to almost 90 percent of the population. However, most of the agricultural production is by small-scale subsistence farmers who engage in non-market production and work under a myriad of production and post-production constraints. The Plan for the Modernisation of Agriculture (PMA) was therefore designed as a strategic framework for eradicating poverty through the implementation of multi-sectoral interventions to tackle the constraints that ordinary farmers face. Specifically, PMA is aimed at increasing income, quality of life, household food security, providing gainful employment, and providing sustainable use and management of resources. In support of PMA priority interventions, the Government of Uganda (GoU) is implementing the Prosperity for All development framework that embraces rural enterprise and promotes industry by building on the Plan for Zonal Agricultural Production, Agro-processing and Marketing. By applying zoning and enterprise selection criteria, PMA hopes to provide information and guidance to local governments and individual farmers on agricultural investments. The Kampala office of the International Food Policy Research Institute (IFPRI), as a principal partner under its Uganda Strategy Support Programme, is assisting the PMA Secretariat in building capacity to select enterprises based on their relative profitability at the agricultural production zone level. The current analysis is in line with this broad objective and is aimed at 1) providing information on the relative profitability of PMA priority enterprises at the agricultural production zone level, and 2) assessing the use of the Uganda National Household Survey (UNHS) for developing partial budgets for PMA priority enterprises.